Improve micro genetic algorithm for multiobjective kursawe function and low pass filter circuit design optimization - Lim, Wei Jer (School of Microelectronic Engineering, 2015)
The main scope of the research work presented in this report is to design and develop a hybrid MOEA for optimizing MOPs. This study presents an investigation on the properties and advantages of MOEAs to develop a novel hybrid evolutionary optimization model. The benchmark studies considered in this research are concerned with the capability to find Pareto optimality. Thus, the research focuses on ZDT and Kursawe test functions which are challenging for finding good Pareto optimality. Last but not least, based on the findings, a multi-objective evolutionary circuit optimizer is developed to assist circuit design parameter tuning. Some circuit evaluations are conducted and the circuit optimizer is designed to integrate cost-saving plug-and-play feature for convenient use of engineers.